The Effect Of Nigella Sativa Administration In Reducing Oxidative Damage In Covid-19 Patients: A Clinical And In Silico Study - Diany, Holly; Nurrasyidah, Ira; Haryati, Haryati; Isa, Mohamad; Kusumawardhani, Erna (Riviera Publishing, 2024)
The COVID-19 pandemic has posed significant challenges to public health, particularly about the oxidative damage caused by infection. Nigella sativa, known for its antioxidant properties, has been extensively studied as a potential therapeutic agent to reduce oxidative damage. This study aims to evaluate the effects of Nigella sativa administration in reducing oxidative damage in COVID-19 patients through a clinical and in silico approach. The research methods include a clinical trial on COVID-19 patients supplemented with Nigella sativa and in silico molecular analysis to identify the interaction mechanisms between the active components of Nigella sativa and SARS-CoV-2 proteins. The results showed that Nigella sativa significantly reduced oxidative stress biomarkers in patients, and in silico results revealed the potential of its active components to inhibit critical enzymes of the SARS-CoV-2 virus. Based on these findings, it is concluded that Nigella sativa has potential as an adjunct therapy in reducing oxidative damage in COVID-19 patients. Further research is required to confirm these results through broader, more in-depth clinical trials.